Retroviral Cyclin Enhances Cyclin-Dependent Kinase-8 Activity - Rovnak, Joel (American Society for Microbiology, 2012)
Alterations in the functional levels of cyclin-dependent kinase-8 (CDK8) or its partner, cyclin C, have been clearly associated with cancers, including colon cancer, melanoma, and osteosarcoma. Walleye dermal sarcoma virus encodes a retroviral cyclin (RV-cyclin) that localizes to interchromatin granule clusters and binds CDK8. It also binds to the Aα subunit (PR65) of protein phosphatase 2A (PP2A). Binding to the Aα subunit excludes the regulatory B subunit, but not the catalytic C subunit, in a manner similar to that of T antigens of the small DNA tumor viruses. The expression of the RV-cyclin enhances the activity of immune affinity-purified CDK8 in vitro for RNA polymerase II carboxy-terminal domain (CTD) and histone H3 substrates. PP2A also enhances CDK8 kinase activity in vitro for the CTD but not for histone H3. The PP2A enhancement of CDK8 is independent of RV-cyclin expression and likely plays a role in the normal regulation of CDK8. The manipulation of endogenous PP2A activity by inhibition, amendment, or depletion confirmed its role in CDK8 activation by triggering CDK8 autophosphorylation. Although RV-cyclin and PP2A both enhance CDK8 activity, their actions are uncoupled and additive in kinase reactions. PP2A may be recruited to CDK8 in the Mediator complex by a specific PP2A B subunit or additionally by the RV-cyclin in infected cells, but the RV-cyclin appears to activate CDK8 directly and in a manner independent of its physical association with PP2A.